Taština nad taštinama… ili: O nekim prirodo-znanstveno-fantastičnim mogućnostima mitologizacije prostora i vremena - Ol'ga Sazontchik ([sic])
Taking as a reference one of the best-known works of science-fiction genre in general and the Soviet nauchnaya fantastika in particular, the novel Monday Begins on Saturday by the Strugatsky Brothers, the author attempts to investigate a special variant of the elaboration of the theme of beginning and end, which (especially in combination with the problems of space and time) seems to be a bizarre mixture of literary-cultural (including intertextual) and natural-scientific approaches to the subject and may be considered as the basic issue of the Strugatskys’ text. Single parts of the text, sequentially and in a multi-faceted connection with each other, develop the themes of internal and external space and time in their constitutive disturbances and infinity. The first part of the novel deals above all with the space outside of the Scientific Research Institute of Sorcery and Wizardry, as well as with the problem of the closure and (non-)transparency of diverse borders. The second so-called story focuses on the peculiarities of the internal spatial and temporal parameters of the institute, its physical and cultural-historical infinity as the main characteristics, and it culminates in the description of the absolute end as the collapse of the whole Universe. The third story is devoted to problems related to the general concept of time, the nature of its flow and the question of fundamental possibility of movement along the axis of this cosmological dimension. On the whole, the Strugatsky Brothers create an impression of some cultural-natural-scientific space-time without limits, or with those far beyond the directly specified place and time of the novel’s storyline.